Деформационные режимы и кинематические обстановки новейшего тектонического разрывообразования в пределах Горного Крыма. 1 - Вольфман, Ю.М. (Геофизический журнал, 2014)
It has been shown on the base of considerable tectonophysical material that producing of up-todate tectonic disruptions within the limits of the Mountain Crimea is specified by broad spectrum of deformational regimes and kinematic environments. The technique of plotting is methodologically substantiated for stereographical models of deformational regimes by averaging the parameters of structural-kinematic parageneses of tectonic disruptions and displacements produced in similar conditions. These models reflect adequately regional environments of producing tectonic disruptions. Quantitative ratio of slickensides in parageneses, which make up the basis of corresponding models specify the measure of effects of these or other deformational regimes on the processes of tectogenesis in the region. The models and examples of shearing, upthrust- and upthrust-displacement deformational regimes are presented and their description is given.